Pace-maker f-channels of sinus node myocytеs as a new therapeutic target for heart rate reduction - E. I. Astashkin; M. G. Glezer (Кардиоваскулярная терапия и профилактика)
Heart pace-maker activity is controlled by highly specialized sinus node (SN) myocytes. This control is linked to functional activity of f-channels providing Na+ and К+ If current. F-channels are activated by plasmatic membrane hyperpolarization in pace-maker cells, at diastolic values of membrane potential. Recent experiments have demonstrated that If current activates slow diastolic depolarization (DD) and regulates the rate of this process, together with endogenous neuromediators and exogenous chemical agents. Decrease in the quantity of open f-channels reduces If current, DD rate and increases threshold membrane potential time. As the result, heart rate (HR) decreases. If current is also controlled by cAMP binding to f-channel proteins. cAMP level in SN myocyte cytoplasma is influenced by autonomous nervous system (ANS) neuromediators. This is the mechanism for ANS regulation of HR in physiological settings. Search for chemical agents selectively targeting f-channels resulted in the development of a new medication, ivabradine (Coraxan®), which is used for angina treatment in patients with sinus rhythm. The medication decreases HR by If current reduction and DD time increase. Importantly, ivabradine does not affect other ion channels.